Comparative study on combustion and emission characteristics on jatropha oil biodiesel with diesel / Mohd Azan Mohammed Sapardi - Mohd Azan , Mohammed Sapardi (2012)
This study is about comparison of combustion and emission characteristics between biodiesel and diesel in internal combustion engine. Study on the performance, combustion and emissions were carried out using Jatropha Oil Biodiesel blends together with conventional diesel (JB10 and JB20) and pure fossil diesel (JB0). The results show that diesel engine operated by Jatropha blends has comparable output with diesel operated engine with different speeds, where the blends give slightly lower output for peak temperature, heat release rate, torque and brake power which is mainly caused by lower heating value of biodiesel compared to diesel. Exhaust emissions such as CO, CO2 and HC seems to be lower for higher blends, credits to the excessive amount of oxygen in the biodiesel to promises cleaner combustion. The heat release rate has an effect on the exhaust emission as it determines the characteristics of flame. Due to analogous combustion and emissions characteristics of Jatropha biodiesel blends and diesel on the same engine type, Jatropha biodiesel blends are feasible to be used in internal combustion engine.